2004
DOI: 10.1021/tx049787n
|View full text |Cite
|
Sign up to set email alerts
|

Lactoperoxidase-Catalyzed Activation of Carcinogenic Aromatic and Heterocyclic Amines

Abstract: Lactoperoxidase, an enzyme secreted from the human mammary gland, plays a host defensive role through antimicrobial activity. It has been implicated in mutagenic and carcinogenic activation in the human mammary gland. The potential role of heterocyclic and aromatic amines in the etiology of breast cancer led us to examination of the lactoperoxidase-catalyzed activation of the most commonly studied arylamine carcinogens: 2-amino-1-methyl-6-phenylimidazo[4,5-b]-pyridine (PhIP), benzidine, 4-aminobiphenyl (ABP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…Aromatic amines are a major class of tobacco carcinogens, which include 2-naphthylamine and 4-aminobiphenyl, two compounds known to cause cancer in both animals and humans (39,40). Epidemiologic studies have provided consistent evidence for a causal relationship between aromatic amines and urinary bladder cancer (41)(42)(43), and experimental studies have shown that aromatic amines are mammary carcinogens in rodents and humans (44)(45)(46)(47). The metabolism of aromatic amines includes the activation and detoxification by metabolic enzymes, such as cytochrome P450s and N-acetyltransferase, and the Nacetylation process by NAT2 is an important detoxification step for aromatic amines (48).…”
Section: Discussionmentioning
confidence: 99%
“…Aromatic amines are a major class of tobacco carcinogens, which include 2-naphthylamine and 4-aminobiphenyl, two compounds known to cause cancer in both animals and humans (39,40). Epidemiologic studies have provided consistent evidence for a causal relationship between aromatic amines and urinary bladder cancer (41)(42)(43), and experimental studies have shown that aromatic amines are mammary carcinogens in rodents and humans (44)(45)(46)(47). The metabolism of aromatic amines includes the activation and detoxification by metabolic enzymes, such as cytochrome P450s and N-acetyltransferase, and the Nacetylation process by NAT2 is an important detoxification step for aromatic amines (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although lactoperoxidase (Gorlewska-Roberts et al, 2004), myeloperoxidase (Uetrecht et al, 1993), and thyroid peroxidase (Gupta et al, 1992) have been shown to bioactivate arylamines to reactive metabolites in vitro, none of these enzymes seems to be expressed in cultured human KCs (Vyas et al, 2006b). However, it is noteworthy that peroxidase inhibition reduces the bioactivation of dapsone in human KC cultures (Vyas et al, 2006b)-substantiating a role for peroxidases in cutaneous bioactivation.…”
Section: Evidence For the Expression Of Drug-metabolizing Enzymes In mentioning
confidence: 99%
“…LPO and MPO) ellipticine can be oxidized to intermediates modifying key molecules such as DNA in this tissue. Hydrogen peroxide, required for peroxidase-mediated oxidations, comes from respiratory burst of neutrophils and is also supplied by xanthine oxidase 65,66 . The finding that ovine COX-1 and human COX-2 are capable of oxidative activation of ellipticine seems to have even greater significance.…”
Section: Oxidation Of Ellipticine By Peroxidases: Another Way To Metamentioning
confidence: 99%